The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Colloidal Quantum Dots for Biomedical Applications V 2010
DOI: 10.1117/12.842925
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle-induced degranulation observed with quantitative phase microscopy

Abstract: The use of AgNP is becoming more and more widespread in biomedical field. But compared with the promising bactericidal function, other physiological effects of AgNP on cells are relatively scant. In this research, we propose quantitative phase microscopy (QPM) as a new method to study the degranulation, and AgNP-induced RBL-2H3 cell degranulation is studied as well. Firstly, HeLa cells as the cell control and PBS as the solvent control, we measured the cell volume and cross section profile (x-z plane) with QPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…To the best of our knowledge, the present study's data demonstrating that AgNP 20 , but not AgNP 70 , promote degranulation in human PMN are the first to be reported in the literature. These results are in agreement with previous studies demonstrating AgNP could induce degranulation in rodent mast cells Yang et al 2010). Although not of human origin, these cells were found to degranulate in response to AgNP with a diameter of 20 nm (at 25 and 50 mg/ml), but not of 110 nm .…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, the present study's data demonstrating that AgNP 20 , but not AgNP 70 , promote degranulation in human PMN are the first to be reported in the literature. These results are in agreement with previous studies demonstrating AgNP could induce degranulation in rodent mast cells Yang et al 2010). Although not of human origin, these cells were found to degranulate in response to AgNP with a diameter of 20 nm (at 25 and 50 mg/ml), but not of 110 nm .…”
Section: Discussionsupporting
confidence: 93%
“…The degranulation of RBL‐2H3 cells has been studied by different microscopies to show their degranulation processes (Huang et al ., ; Yang et al ., ). But the limited resolution of light microscopy still restricts our understanding of the detailed degranulation processes of RBL‐2H3 cells.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, other studies have observed that the toxicity of silver NPs versus Ag + ions on mammalian cells showed significant toxic effects starting from 200 nM NP concentration [ 35 ], which suggests that our NPs are more toxic. Literature also suggests that other effects on the rat basophilic leukemia cells, such as degranulation, may occur [ 39 ]. We would like to add, that according to the experimental evidence presented in this work the origin of the photoluminescence of silver nanoclusters reported in previous publication [ 40 ] must be glycine dimers, and not the intrinsic emission of the silver clusters, as we suggested before.…”
Section: Resultsmentioning
confidence: 99%